Students' perceptions regarding the use of ICT in learning (Proceedings of the International Conference on Education, 2019)
This study focuses on how students of vocational courses related to Information and Communication Technologies (ICT) perceive the use they make of technologies in their learning. A questionnaire survey was applied in classroom to 314 students from 4 private and public schools, with the aim of understanding if the students recognize benefits in the use of ICT in teaching and learning, by answering the 34 premises presented to them. Most students recognize benefits from the use of ICT in teaching considering it improves and facilitates learning. They recognize the need to improve the pedagogical use of ICT and that teachers from the scientific and sociocultural components still make little use of the technologies in the classroom. These students consider that the courses they take prepare them to integrate the labor market, indicating good practices in learning with and from technologies in the technical classes. The premises about the disadvantages and obstacles resulting from the use of ICT were the ones that gathered the lowest consensus among students. They consider that the use of ICT is essential in learning and preparing to work with ICT and in a broader sense to live in a society of information and knowledge.
Keywords: Students' perceptions, Information and Communication Technology; Learning